Chloroplast genome sequence of the wild Ziziphus jujuba Mill. var. spinosa from North China - Yuping Zhang; Guanglong Hu; Weitao Mao; Ningguang Dong; Bo Chen; Qinghua Pan (Mitochondrial DNA. Part B. Resources, 2021)
In this study, the complete chloroplast (cp) genome sequence of Ziziphus jujuba Mill. var. spinosa was mapped and determined based on Illumina sequencing data. The complete cp genome is 161,606 bp and contains a pair of inverted repeat regions of 26,479 bp each, a large single-copy region of 89,292 bp, and a small single-copy region of 19,356 bp. It harbors 112 unique genes, including 78 protein-coding genes, 4 ribosomal RNA genes, and 30 transfer RNA genes. Phylogenetic analysis based on cp genomes indicates that the cp genome of wild Z. jujuba Mill. var. spinosa is similar to that of cultivated Z. jujuba and closely related to that of Z. incurva of the family Rhamnaceae.